Nafertisite, a layer titanosilicate member of a polysomatic series including mica - G. Ferraris; G. Ivaldi; A. P. Khomyakov; S. Soboleva; E. Belluso; A. Pavese (Schweizerbart'sche Verlagsbuchhandlung, 1996)
Nafertisite, (Na,K)3(Fe2+,Fe3+,□)10[Ti 2(Si,Fe3+,Al)12O37](OH,O) 6, is an alkaline titanosilicate from the Khibina massif (Kola Peninsula, Russia). It is monoclinic A2/m with a = 5.353(4), b = 16.176(12), c = 21.95(2) Å, ß = 94.6(2)°, Z = 2. The comparison with bafertisite, Ba2(Fe,Mn)4[Ti2Si4O 17](OH,O)3, and astrophyllite, (K,Na)3(Fe,Mn)7 [Ti2Si8O27](OH,O)4, allowed to obtain a structural model for nafertisite which has been tested against X-ray diffraction data obtained from a very poor crystal. On the basis of a bafertisite-like B module (A,□)2(M,□)4 [X2T4O17](OH)2 and a mica-like M module (A,□)(M,□)3[T4O10](OH)2, a polysomatic series BMn can be defined where bafertisite, astrophyllite, nafertisite and mica are the members with n = 0, 1, 2, ∞, respectively. It is called heterophyllosilicate series because the crystal structures of the members consist of 2:1 HOH layers where O is an octahedral sheet and H is a tetrahedral-like sheet which differs from the T sheet of the phyllosilicates for the insertion of Ti octahedra; these play a role similar to that of Si tetrahedra. A group of titanosilicates is shown to be derivatives of the bafertisite structure with different interlayer contents.